Performance of Barbari goats under different systems - PATEL, M S; SINGH, N P; GEHLAUT, B S; SINGH, H S (The Indian Journal of Animal Sciences, 2014)
The physiological responses of goats were measured weekly in the morning and evening during summer and winter. Significantly (P< 0.01) higher rectal temperature was observed in the morning in summer as compared to that in the winter in both grazing and stall-feeding groups. The evening rectal temperature was, on the other hand, significantly (P